The Influence of Hexahelix Model on The Sustainability of MSMEs: The Moderating Effect of Frugal Strategy - Richo Diana Aviyanti; Nik Amah; Elly’s Mersina Mursidik (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Background Problem: Existing studies have largely examined Hexahelix collaboration or frugal innovation separately, providing limited empirical evidence on how frugal strategy enhances the effectiveness of multi-actor collaboration in supporting MSME sustainability, particularly in medium-sized cities. Novelty: This study contributes by integrating the Hexahelix model and frugal strategy into a single empirical framework, positioning frugal strategy as a moderating variable. It also provides evidence from Madiun City, Indonesia, a regional context that remains underrepresented in sustainability research. Method: A quantitative survey was conducted among 180 MSMEs selected through purposive sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Results/Findings: The results reveal that the Hexahelix model significantly improves MSME sustainability. Frugal strategy not only has a positive direct effect on sustainability but also strengthens the influence of Hexahelix collaboration by enabling MSMEs to transform external support into resource-efficient, environmentally friendly, and competitive business practices. Conclusion: The findings extend the Hexahelix framework by demonstrating that collaborative success depends on both stakeholder synergy and MSMEs' internal frugal capabilities. Integrating collaborative governance with frugal strategies can enhance MSME competitiveness while promoting long-term economic, social, and environmental sustainability.